Multiple approaches for the management of Alzheimer disease: Natural compounds, FDA approved drugs, and nanotechnology interventions: Approaches for the management of Alzheimer's disease - Leena Esam Azhar,; Abdulrahman Esam Azhar,; Najiah Esam Azhar, (Cellular and Molecular Biology, 2022)
Alzheimer's disease is the most common in the elderly population. Due to its irreversible and progressive nature, it gained more attention for early management. In this regard, several new therapeutic targets, such as degrading neurotransmitter enzymes, amyloid cascade enzymes, and monoamine oxidases, have been explored. Inhibition of these targets with natural and synthetic compounds and dietary supplements has been traditionally exercised for decades in the etiology of AD. Secondary metabolites obtained from natural resources are in the trend to use against these targets. The purpose of this review is to provide a brief introduction to AD along with the related concept of several therapeutic compounds involved in the progression of the disease and its management using different natural compounds against selected targets.